2012
DOI: 10.2478/s13545-012-0018-y
|View full text |Cite
|
Sign up to set email alerts
|

Mercury distribution in muscles and internal organs of the juvenile and adult Baltic cod (Gadus morrhua callarias Linnaeus, 1758)

Abstract: Cod (Gadus marrhua L), a fish caught in the Baltic Sea, is very popular with consumers. Research on the distribution of mercury in cod tissues and organs was conducted on a group of adult (27) and juvenile (49) individuals in the years 2006-09. Total mercury concentration values in mature cod were always, on average, 1.7 times higher than those in juveniles. The highest HgT concentrations were found in the heart, while the lowest ones were found in the gills and gonads. The essential age-specific differences m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Hence, liver is a good indicator of marine environmental pollution. Researchers pointed out the importance of liver in processes of storing, redistributing, detoxifying, and transforming contaminants depending on age and sex (Burger and Gochfeld 2007 ; Havelková et al 2008 ; Kwaśniak and Falkowska 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, liver is a good indicator of marine environmental pollution. Researchers pointed out the importance of liver in processes of storing, redistributing, detoxifying, and transforming contaminants depending on age and sex (Burger and Gochfeld 2007 ; Havelková et al 2008 ; Kwaśniak and Falkowska 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The negative correlation between OP and NP concentrations in muscles and the weight of cod (Table 6 ) was probably influenced by the lower fat content in cod compared with herring and flounder (Reindl et al 2013 ; Kwaśniak and Falkowska 2012 ). The observed liver/muscle concentration ratio for NP and OP, which in cod increased with weight (age), could have resulted from the length of exposure to xenobiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Organic mercury usually dominates in the muscles of fish, and concentrations are usually significantly correlated with fish age and weight (Polak-Juszczak 2017 ). Methylmercury is the strongest of the neurotoxins, and it is mutagenic and causes disruptions in the circulatory system, the nervous system, reproductive parameters, and spawning (Hammerschmidt et al 2002 ; Kwaśniak and Falkowska 2012 ). Changes in biochemical processes in fish occur at concentrations of CH 3 Hg + from 0.5 to 1.2 μg g −1 w.w. in dorsal muscle (Dietz et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates dominance of detoxification over accumulation processes. Several studies have shown that the liver has the ability to accumulate large amounts of pollutants from the external environment and plays an important role in their storage, redistribution, detoxification and transformation (Evans et al 1993;Wiener et al 2003;Kwaśniak, Falkowska 2012). No fungicides were found in the liver.…”
Section: Resultsmentioning
confidence: 99%